MARKET PERSPECTIVES AND SUSTAINABLE AGRICULTURE IN THE CASE OF THE REPUBLIC OF SERBIA - Ignjatović, Jelena; Bajagić, Marija; Blagojević, Milan (Economics of Agriculture, 2025)
Sustainable agriculture (SA) represents an ecological and economic development path with the aim of applying the best agricultural practices and technologies for the production of healthy food, increasing productivity and competitiveness on the market. The aim of the work is to research the perspectives of the market and SA in the territory of Serbia - Mačva. The research was conducted through a survey with 26 questions and 110 respondents. Analysis of the results shows that young people (50%) are familiar with the concepts of SA (57%) and circular economy (50%). Respondents are interested in SA, purchasing products or starting production, with the main motives: health and environmental protection. The main problems are the high price and poor financial support. For the development of sustainable agriculture, education on the implementation of the circular economy in sustainable agriculture systems, financial support and the availability of the necessary inputs for production are necessary.